THE EJECTORS FANS INSTALLED IN THE MINES ON THE NORTH-EAST RUSSIA - Alymenko, N.I.; Kamenskikh, A.A. (Perm Federal Research Centre Journal, 2016)
This publication describes the results of theoretical modeling, experimental studies and the results of industrial use of mobile underground fan (MUF). MUF may be used for degassing system of mine workings in emergency situations, and by the example of mine "MNV" (JSC "MNV") and "Ducat" (JSC "Magadan Silver") the results show the possibility of using MUF as the main fan installations (MFI). Axial fans and centrifugal fans can be used for MUF.